Time to clinical improvement: an appropriate surrogate endpoint for pulmonary arterial hypertension medication trials - Wang, An; Chen, Mengqi; Zhuang, Qi; Guan, Lihua; Xie, Weiping; Wang, Lan; Huang, Wei; Cheng, Zhaozhong; Yu, Shiyong; Zhou, Hongmei; Shen, Jieyan (Frontiers in Cardiovascular Medicine, 2023)
Background: Many retrospective studies suggest that risk improvement may be suitable efficacy surrogate endpoints for pulmonary arterial hypertension (PAH) medication trials. This prospective multicenter study assessed efficacy of domestic ambrisentan in Chinese PAH patients and observed risk improvement and Time to Clinical Improvement (TTCI) under ambrisentan treatment. Methods: Eligible patients with PAH were enrolled for a 24-week treatment with ambrisentan. The efficacy primary endpoint was Δ6MWD. The exploratory endpoints were risk improvement and TTCI, defined as the time from initiation of treatment to first occurrence of risk improvement. Results: A total of 83 subjects were enrolled. After ambrisentan treatment, Δ6MWD was significantly increased at week 12 (42.2 m, P < 0.0001) and week 24 (53.4m, P < 0.0001). Within 24 weeks, Risk improvement was observed in 53 (64.6%) subjects (P < 0.0001), which is higher than WHO-FC (30.5%) and TAPSE/PASP (32.9%). Kaplan-Meier analysis of TTCI showed a median improvement time of 131 days and a cumulative improvement rate of 75.1%. And TTCI is consistent across different baseline risk status populations (Log-rank P = 0.51). Naive group had more risk improvement (P = 0.043) and shorter TTCI (Log-rank P = 0.008) than add-on group, while Δ6MWD did not show significant difference between two groups. Conclusions: Domestic ambrisentan significantly improved exercise capacity and risk status in Chinese PAH patients. TTCI has a relatively high positive event rate within 24 weeks treatment duration. Compared to Δ6MWD, TTCI is not affected by baseline risk status. Additionally, TTCI could identify the better improvements in patient which are not detected by Δ6MWD. TTCI is an appropriate composite surrogate endpoint for PAH medication trials. Trial registration: NCT No. (ClinicalTrials.gov): NCT05437224.